2020
DOI: 10.3390/ijms21134644
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Production of Human Skin Equivalent in 3D, Multi-Cell Culture

Abstract: An important problem for researchers working in the field of dermatology is the preparation of the human skin equivalent (HSE). Here, we describe a simple and reliable protocol for preparing a skin model from the commercially available cell lines: keratinocytes, fibroblasts, and melanocytes. Importantly, in our 3D model, the keratinocytes are diverse that brings this model closer to the natural skin. For the production of HSE, we used available primary PCS-200-010, PCS-201-010, PCS-200-013, and immortalized CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…These results were confirmed by Penna et al [ 32 ]. Taken together, these confirm the hypothesis that in some cases reconstructed skin tissues may be a good substitute for conducting effective skin tests, especially when the morphology of natural skin is preserved, [ 33 ]. It has been shown that exposure to UV light might regulate epidermal keratinocytes autophagy through selective down-regulation of key autophagy-related genes including ULK1, ATG3, ATG5, and ATG7 [ 34 ].…”
Section: The Uv Light (10–400 Nm)supporting
confidence: 77%
“…These results were confirmed by Penna et al [ 32 ]. Taken together, these confirm the hypothesis that in some cases reconstructed skin tissues may be a good substitute for conducting effective skin tests, especially when the morphology of natural skin is preserved, [ 33 ]. It has been shown that exposure to UV light might regulate epidermal keratinocytes autophagy through selective down-regulation of key autophagy-related genes including ULK1, ATG3, ATG5, and ATG7 [ 34 ].…”
Section: The Uv Light (10–400 Nm)supporting
confidence: 77%
“…There is an emerging consensus that 3D skin models are now favored over both animal models and 2D cellular models due to their architecture that physiologically resemble the native human skin (Klicks et al, 2017;Szymański et al, 2020). The biggest advantage of 3D skin models over 2D models is their 3D assembly that reconstructs the physiological features found in vivo (Klicks et al, 2017).…”
Section: Three-dimensional Tissue Culture Modelmentioning
confidence: 99%
“…The development of advanced 3D-culture methods, with well-differentiated cell types (e.g., keratinocytes, fibroblasts, and immune cells) representing an artificial replicate of multi-layered human skin, has been particularly relevant for the topics treated in this work, as it allowed for the study of interactions among commensal, opportunistic, and pathogenic bacteria, and the investigation of critical processes such as wound healing and biofilm formation [ 166 , 167 ].…”
Section: Methodological Considerations On Ngs Techniquesmentioning
confidence: 99%